A RANDOMIZED CONTROLLED CLINICAL STUDY OF KARANJADHYA GHRITA ON ACUTE WOUNDS WITH SPECIAL REFERENCE TO ITS WOUND HEALING PROPERTIES - Choudhary, Neelam; Soni, Prashant; Narode, Sagar; Swarnkar, Madhusudan (International Journal of Ayurveda and Pharma Research, 2015)
Background: Acute wounds are frequently encountered problem in the present era produced due to trauma or pathological injury. Chakradutt has mentioned the wound healing properties of Karanjadhya Ghrita. In the present study Karanjadhya Ghrita was prepared and its wound healing properties were studied on various acute wounds. Methods: Karanjadhya Ghrita was prepared using the standardization procedure the effects were studied on 40 patients selected from Outpatient and Inpatient department of Shalya Tantra, National Institute of Ayurveda, Jaipur. The patients were divided into two groups. Group A (Karanjadhya Ghrita dressing) and Group B (Hydrogen peroxide and EUSOL and dry Gauze bandage). The drug was applied topically and patients were studied daily for 30 days and results were analyzed. Results: It was noticed that 70% of acute wound patients were cured. 100% cured result was observed in all cases of lacerated wound, fissure, burn, wart and Pressure sores. Conclusion: From the studies made from clinical cases, it was concluded that, the drug Karanjadhya Ghrita possess sufficient efficacy in Vrana Shodhan and Vrana Ropana properties without producing any adverse effects. The drug also increased the rate of contraction producing healthier granulation tissue and rapid healing time. Hence, this study concludes that application of Karanjadhya Ghrita is highly effective on acute wounds.